1991
DOI: 10.1016/0020-7373(91)90019-4
|View full text |Cite
|
Sign up to set email alerts
|

Animated demonstrations vs written instructions for learning procedural tasks: a preliminary investigation

Abstract: Animated demonstrations have been created due to the development of direct manipulation interfaces and the need for faster learning, so that users can learn interface procedures by watching. To compare animated demonstrations with written inst~~ions we observed users learning and performing HyperCardTMS authoring tasks on the Ma~nt~h~ during three performance sessions. In the training session, users were asked either to watch a demonstration or read the procedures needed for the task and then to perform the ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
3
2

Year Published

1993
1993
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(78 citation statements)
references
References 14 publications
0
73
3
2
Order By: Relevance
“…Palmiter and colleagues compared animated and still graphics for teaching students how to use an on-line help system for Hypercard 1 (Palmiter, Elkerton & Baggett, 1991;Palmiter & Elkerton, 1993). Although the students using the animation completed the training task more quickly, they completed the testing task more slowly.…”
Section: Failures Of Animation To Benefitmentioning
confidence: 99%
“…Palmiter and colleagues compared animated and still graphics for teaching students how to use an on-line help system for Hypercard 1 (Palmiter, Elkerton & Baggett, 1991;Palmiter & Elkerton, 1993). Although the students using the animation completed the training task more quickly, they completed the testing task more slowly.…”
Section: Failures Of Animation To Benefitmentioning
confidence: 99%
“…However, many studies have found that animations by themselves do not improve performance (Byrne, Catrambone, & Stasko, 1999;Mayer & Anderson, 1991;Palmiter & Elkerton, 1993;Palmiter, Elkerton, & Baggett, 1991;Rieber, Boyce, & Assad, 1990) unless they provide more information than static images (Pane, Corbett, & John, 1996;Tversky, Morrison, & Betrancourt, 2002). The finding that animations by themselves do not improve performance has led many researchers to question their usefulness (Palmiter & Elkerton, 1993;Pane et al, 1996), suggesting that animations should be used only in very limited situations, i.e.…”
Section: Security Classification Of: 17 Limitation Of Abstractmentioning
confidence: 99%
“…only when necessary and when the animation is not too difficult to use (Betrancourt & Tversky, 2000). But most of these studies have been performed in laboratory settings (e.g., Kaiser, Proffitt, Whelan, & Hecht, 1992;Palmiter et al, 1991) or use tasks specially crafted to show animated or static pictures (e.g., Pane et al, 1996;Rieber, 1991 (Palmiter & Elkerton, 1993), to teach computer science algorithms (Byrne et al, 1999) to teach how something works (Mayer & Anderson, 1991;Pane et al, 1996), and to understand other complex dynamic systems, like the weather (Lowe, 1999). Indeed, the prevalent feeling in this body of literature is that animations should be better than static images because, by a principle of congruence, animations should be a natural medium for conveying information about change, just as graphics are a natural way for conveying information about space (Tversky et al, 2002).…”
Section: Security Classification Of: 17 Limitation Of Abstractmentioning
confidence: 99%
“…The 3d images are viewed with cardboard glasses containing one red and one blue lens. page 14 (5) Simulation (5) Other (7) ACSE 73 (9) 70 (12) 78 (10) 72 (10) Control 71 (9) 72 (14) 71 (9) 71 (10) …”
Section: Performance On Review Questionsmentioning
confidence: 99%
“…But similar studies in physics learning did not find significant improvements [ 11], [12]. There is evidence that use of movies may result in speed improvements on immediate recall tasks, but that the effect is reversed on long term recall tasks [9]. But even in cases where improvements are slight, students have a high perceived value of movies [1], [14].…”
Section: Introductionmentioning
confidence: 99%